Synergistic Effect of Retinoic Acid Polymeric Micelles and Prodrug for the Pharmacodynamic Evaluation of Tumor Suppression - Zhu, Yan-Hua; Ye, Ning; Tang, Xin-Feng; Khan, Malik Ihsanullah; Liu, Hong-Liang; Shi, Ning; Hang, Li-Feng (Frontiers in Pharmacology, 2019)
All-trans-retinoic acid (ATRA) is a very effective agent for inducing differentiation, inhibiting cell proliferation and reported as an anti-cancer agent. ATRA was successfully conjugated with pluronic-127 by esterification to enhance the ATRA anticancer effect. Pluronic-ATRA possessed high cytotoxicity and could efficiently reduce the IC50 value of ATRA against different breast cancer cells (4T1, EMT6, MDA-MB-231 and BT474). In combination with chemotherapy, pluronic-ATRA synergistically enhanced the cytotoxic effect of cisplatin (CDDP). Pluronic-ATRA combined with CDDP could effectively suppressed breast tumor in vivo. This study suggested the potential of pluronic ATRA, which can be used as an anticancer agent in combination therapy against solid tumor.